Role of Learning Resources in Managing the Learning Behavior of Students in Diverse Classroom - Shahi, Bhupendra Bahadur (Journal of Gurubaba, 2025)
The main purpose of this research paper was to explore the role of learning resources in managing the learning behavior of students in diverse classroom. The paper was based on the analysis and discussion of the writer’s claim relating with the findings of the related literature. Different themes and contents were analyzed relating with suitable literatures. The paper revealed that promoting student’s engagement in learning, promoting active learning to the students, encouraging group interaction, encouraging student’s creativity, encouraging the student to work independently and confidently, and changing positive learning behavior of the students were the main roles of learning resources in managing learning behavior of student in diverse classroom. The paper showed that learning resources support to the students to managing and modifying the learning behavior. Appropriate learning resources encourage the students to learn effectively, confidently, independently, and freely in the diverse classroom. The paper also found that learning behavior could not be managed without using the learning resources with properly.